Accelerating Simulations of Cardiac Arrhythmias through Robust Numerical Techniques and Parallel Computing - Couto, Guilherme M.; Monteiro, Noemi Z.; Santos, Rodrigo W. dos (Anais Estendidos do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2023)
This paper explores how numerical methods and parallel computing can be used to accelerate simulations of cardiac arrhythmia. The simulations are based on the monodomain cardiac model, governed by a set of partial differential equations (PDEs). The new software could accurately reproduce various types of arrhythmia, such as spiral waves and reentry, by solving the PDEs using an Alternating Direction Implicit (ADI) fractional splitting method. Parallel programming via OpenMP led to a significant reduction in computation time, making the simulations feasible for practical applications.